Female Objectification in Billie Eilish’s “Male Fantasy” - Adinda Desti Nur Arrizqo; Randi wira Pramestya; Muhammad Rezha Syahputra; Muhammad Varra Ramadhan; Ahsin Hamdi Habibie (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2026)
This study explores the psychological impact of female objectification as reflected in Billie Eilish’s song “Male Fantasy.” Despite significant social progress in gender equality, women continue to experience objectification, where their value is assessed primarily based on appearance rather than individuality or competence. Drawing upon Fredrickson and Roberts’ Objectification Theory (1997), this research examines how objectifying cultural messages are internalized by women and manifest in self-perception, emotional experiences, and behavior. The study employs a qualitative approach using thematic content analysis of the song’s lyrics, focusing on expressions related to self- objectification, body surveillance, body shame, and emotional distress. The analysis reveals that the lyrics vividly illustrate the internalization of societal beauty standards and patriarchal expectations, with the protagonist frequently monitoring her body, expressing dissatisfaction, and experiencing feelings of inadequacy and emotional strain. Findings indicate that music, as a cultural medium, not only reflects the pressures of female objectification but also provides insight into its psychological consequences. The song’s melancholic tone and introspective lyrics serve as a powerful representation of how women navigate the tension between societal ideals and authentic emotional experiences. This study contributes to the literature by highlighting the underexplored domain of lyrical content in examining female objectification, offering theoretical and practical implications for understanding the pervasive impact of objectifying messages on women’s mental health. Future research may extend this approach to additional media forms to further investigate the relationship between cultural representation and psychological well-being in women